2021
DOI: 10.1007/s11255-021-03076-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trajectories of SARS-CoV-2 neutralizing antibodies and predictive value of first dose vaccination-induced IgG-antibodies in hemodialysis patients

Abstract: Purpose The predictive value of antibody titers after the first SARS-CoV-2 vaccination and long-term trajectories of antibody titers in hemodialysis patients are unknown. Methods SARS-CoV-2 IgG antibodies and their neutralizing effect six weeks after the first and second vaccination were analysed in 30 hemodialysis patients. IgG titers served to classify participants as responders or non-responders and to calculate sensitivity, specificity, and accuracy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the kinetics of antibody waning after vaccination is poorly understood in this group of patients. A few studies indicate a faster decline in the neutralizing antibody titer in dialysis patients than in the general population [ 20 ]. It is not fully known what vaccination schedule against COVID-19 is optimal for dialysis patients, and at what number of doses and in what intervals it should be administered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the kinetics of antibody waning after vaccination is poorly understood in this group of patients. A few studies indicate a faster decline in the neutralizing antibody titer in dialysis patients than in the general population [ 20 ]. It is not fully known what vaccination schedule against COVID-19 is optimal for dialysis patients, and at what number of doses and in what intervals it should be administered.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to long-term humoral immunity after vaccination, several studies among health care workers have reported that SARS-CoV-2 spike protein antibody titers and neutralizing antibodies progressively decline up to 6 months after vaccination [ 3 , 4 , 37 , 38 ]. Studies of HD patients in Germany showed that SARS-CoV-2 spike protein antibody titers peaked 1 month after the second vaccination in dialysis patients and declined to approximately 50% of peak values 3–4 months later [ 5 , 23 , 39 ]. The results of the present study showed that 6 months after the second dose of the BNT162b2 vaccine, SARS-CoV-2 spike protein antibody titers were markedly decreased (approximately one-seventh) compared with the peak value 1 month after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot comment on titer evolution in patients with third booster vaccinations who already had titers higher than 433 BAU/mL after the second dose. Nevertheless, one might speculate that repeat vaccinations may result in decreased waning of antibody titers as described in different other patient populations [ 25 ] and dialysis patients [ 26 , 27 ]. Despite rapid titer waning, Clarke et al were able to confirm a longstanding SARS-CoV-2 antigen–specific T-cell response in patients without detectable antibody titers six months post vaccination [ 28 ].…”
Section: Discussionmentioning
confidence: 99%